INFLUENCE OF MAGNETIC FIELD ON THE ANTIWEAR PROPERTIES OF DIESEL FUELS REFORMULATED BY BIOCOMPONENTS - Trofimov, Ihor; Svyryd, Mikhailo; Tsyhanenko, Vitalii; Makarov, Artem (Problems of Friction and Wear, 2023)
The article discusses the issue of antiwear properties of traditional and alternative diesel fuels. The main goal of this work was the theoretical and experimental studies on the effect of alternative biodiesel fuels (on a plant basis) on the change in the antiwear properties of traditional diesel fuels. Also, the goal was to study the effect of the magnetic field on the antiwear properties of diesel and alternative diesel fuels. Experimental studies have been conducted for the antiwear properties of traditional and alternative diesel fuels based on biocomponents obtained from rye oil. The studies showed that the addition of methyl esters of fatty acids of rye oil led to an increase in the amount of wear by 1.8 (10% esters) and 2.2 (20% esters) for the diesel samples and their mixtures with biocomponents, respectively. During the treatment of fuels with a magnetic field of 0.1 T and 0.4 T, it was established that the amount of wear is 1.2 and 1.5 times (10% esters, a magnetic field of 0.1 T and 0.4 T, respectively); 2.2 and 1.15 times (20% esters, magnetic field of 0.1 T and 0.4 T, respectively) times, respectively. It was established that the treatment with a magnetic field stabilizes the antiwear properties of diesel fuels in the case of addition a biological component to them. The results of studies can be applied in the chemical industry, the transport industry, in particular, in the operation of diesel vehicles. The article results can be useful to tribologists, chemical experts, as well as scientists involved in the development and implementation of alternative engine fuels.